Vaccination ARN messager (ARNm), modèle de transition de la biologie fondamentale à la médecine - Sansonetti, Philippe J. (Comptes Rendus Biologies, 2024)
Sixty years elapsed between the discovery of messenger RNA (mRNA) and the use of this molecule in an unprecedented global vaccination campaign that brought the Covid-19 pandemic under control. Sixty years of doubts for some and certainties for others about the possibility of using mRNA—an example of synthetic biology—in therapeutic medicine and vaccinology. Years of “translational” research and development have culminated in the success of anti-Covid-19 mRNA vaccines and the promise of more to come against emerging pathogens. A new paradigm in vaccinology, enabling pandemics to be tackled as they emerge. A lesson to be learned: medical progress is less a question of time than of the critical nature of the biological discovery that underpins it. Before leaving us, François Gros, who played a key role in the discovery of mRNA, was able to appreciate the relevance of this obvious fact.